Pluralism as cosmopolitanism - Calvo de Saavedra, Ángela (Estudios de Filosofía, 2008)
Pluralism as a factum is an ethical pluralism, of conceptions of a good life -religious or not-, while pluralism as a regulative idea is a political task that, from modernity to the present, requires thought and imagination. To address the theme that brings us together in this Congress, I propose to take into account the two edges -descriptive and normative- of pluralism, that is, to assume that the conditions of difference in the modern world were neither as many nor the same as the present, that is, to attend to the undeniable expansion of the geographical scene and of the movements and groups that want to affirm their identity in the face of a hegemonic culture. Such cartography invites us to reconstruct the normative intuitions of political liberalism -first version of response to the challenge of ethical pluralism- to its most elaborate version in contemporary debate, with the aim of investigating whether they can serve as a model to face the challenges of the present. I will do so from the proposal of Jürgen Habermas, in my opinion not only one of the clearest defenders of liberalism, but the architect of one of the most solid and innovative versions of this tradition. [Fragment]